Activation and Deactivation of the Polymerization of Ethylene over rac‐EtInd2ZrCl2 and (nBuCp)2ZrCl2 on an Activating Silica Support. Issue 14 (3rd June 2014) - Tisse, Virginie F.; Boisson, Christophe; McKenna, Timothy F. L.
<x xml:space="preserve">Abstract</x> A study is carried out in order to better understand the kinetic behavior of two different metallocene precursors supported on an activating silica support, and, in particular, to attempt to reduce the significance of catalyst deactivation through the use of different alkylating agents. It is observed that it is difficult to prevent the deactivation of the rac‐EtInd2ZrCl2 sites on the activating support, and, furthermore, the deactivation is accompanied by the disappearance of sites producing the highest‐molecular‐weight polymer. On the contrary, with the (nBuCp)2ZrCl2 precursor, it is possible to manipulate the addition of either tri‐isobutylaluminum (TIBA) or triethylaluminum (TEA) to significantly reduce the deactivation of the catalyst on the activating supports. Finally, the molecular‐weight distribution seems to depend much more on the intrinsic properties of the active sites than on how the active sites are treated. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>